If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-6 + -1x) = -30 (-6 * 3 + -1x * 3) = -30 (-18 + -3x) = -30 Solving -18 + -3x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -3x = -30 + 18 Combine like terms: -18 + 18 = 0 0 + -3x = -30 + 18 -3x = -30 + 18 Combine like terms: -30 + 18 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 3(2.5+-0.5y)-3y=3 | | 3+3x+1x=23 | | 6x^6-5x^3-1=0 | | 3x-8-3x-2=6 | | 6x+9+4x=19 | | 14f=14 | | 62-d=12 | | 1-7x+3x=-31 | | 66=22m | | 15b=225 | | e=mcqeur | | 4(9-2x)=4 | | -6x+5+3x=26 | | 77-a=12 | | 5y^2-8y=3 | | 4(-2x+5)=-26 | | (x*4)+6=18 | | 20x^3+6x^2-2x+1=0 | | 2(3+2x)=-26 | | -6(2.4+0.4y)-2y=-14 | | X^2-2kx+3k+2=0 | | -6(2.4+-0.4y)-2y=-14 | | (x-8)(x-3)=30 | | .75(20+6y)-.5(18-9y)= | | N+N=N(n) | | Z^2-z+1-i=0 | | 5x-10y-2=0 | | 7m+5=21-3m | | 6(2.92)-3y=14 | | 4x^2+16-18=0 | | 2x^3+5X-18=0 | | 5-7(12)-15= |